Exploring the Role of Domesticated Bio-Resources in Shaping the Economy of Batadraba Village in Nagaon District of Assam - Arup Jyoti Bora; Amrit Borah; Monija Nasrin (The Bioscan, 2024)
With an emphasis on a rural hamlet, this study investigates how domesticated faunal bioresources influence rural communities' patterns of subsistence. The study looks into how domesticated animals like cattle and poultry are used in farming, food production, revenue generation, and cultural customs. The study emphasizes these animals' importance in maintaining rural lives by examining their social, nutritional, and economic aspects. The study also looks at issues that communities face, such as environmental changes, breeding methods, and disease control. In addition to providing insights into sustainable practices that can improve the long-term viability of rural economies and food systems, the findings highlight the significance of domesticated faunal bioresources in promoting rural resilience.